Novel Analysis of Immune Cells from Nasal Microbiopsy Demonstrates Reliable, Reproducible Data for Immune Populations, and Superior Cytokine Detection Compared to Nasal Wash. - Simon P Jochems (PLoS ONE, 2017)
The morbidity and mortality related to respiratory tract diseases is enormous, with hundreds of millions of individuals afflicted and four million people dying each year. Understanding the immunological processes in the mucosa that govern outcome following pathogenic encounter could lead to novel therapies. There is a need to study responses at mucosal surfaces in humans for two reasons: (i) Immunological findings in mice, or other animals, often fail to translate to humans. (ii) Compartmentalization of the immune system dictates a need to study sites where pathogens reside. In this manuscript, we describe two novel non-invasive nasal mucosal microsampling techniques and their use for measuring immunological parameters: 1) using nasal curettes to collect cells from the inferior turbinate and; 2) absorptive matrices to collect nasal lining fluid. Both techniques were well tolerated and yielded reproducible and robust data. We demonstrated differences in immune populations and activation state in nasal mucosa compared to blood as well as compared to nasopharyngeal lumen in healthy adults. We also found superior cytokine detection with absorptive matrices compared to nasal wash. These techniques are promising new tools that will facilitate studies of the immunological signatures underlying susceptibility and resistance to respiratory infections.